07.03 Behçet's disease and hla-b51 in ireland. (1st March 2017) - Adeeb, Fahd; Ugwoke, Adaeze; Devlin, Joseph; Stack, Austin; Fraser, Alexander
Abstract : Background: Behçet's disease (BD) is a type of vasculitis with distinctive clinical manifestations and multifactorial immunopathogenesis. Association of HLA-B51 (which belongs to the HLA-B5/B35 cross-reacting group) is well recognised as the strongest genetic susceptibility gene so far in BD. Aim: The aim of this study is to determine the association of HLA-B51 in our BD cohort in the Midwest region of Ireland. Methods: Patients meeting the ISGBD or the ICBD criteria for BD were identified from our institutional database. Medical charts and electronic data were reviewed retrospectively to document the HLA antigen profile of the patients (which were carried out by a same recognised lab in London using Gen-Probe Lifecodes HLA-SSO Typing kits based on Luminex xMAP technology). Results: 22 patients of Irish descent were identified satisfying the diagnosis for BD, and among them 19 patients (6 males, 13 females) were HLA typed. The HLA-B51 antigen was found in only one of the 19 patients (5.3%) with a higher frequency HLA-B*08, B*44 (6 patients each; 31.6%), B*35, B*57 (5 patients each; 26.3%), B*15 (4 patients; 21%) and B*27 (3 patients; 15.8%). We found no association between HLA-B*51 and our Irish cohort of BD patients compared to control. Conclusion: The overall frequency of HLA-B51 is not increased in our BD cohort. We acknowledge that the study is subject to several limitations including small sample size. Further study of a larger patient population is needed, which may include combination of BD cohorts throughout the country, which will be important to substantiate, support or refute this finding.